Deep eutectic solvent strategy for green extraction of chlorogenic acid from sea buckthorn: optimization and sustainability - Iqra Saddique; Sumia Akram; Saima Rubab; Ayesha Sadiqa; Ali Raza; Muhammad Mushtaq; Mohsin Ahmad Ghauri (SpringerOpen, 2024)
Abstract Background Sea buckthorn (Hippophae rhamnoides), a deciduous species plant, is widely distributed around the globe, and native to the cold-temperate regions of Europe and Asia. This medicinal herb contains several bioactive constituents including chlorogenic acid. The conventional methods used for the extraction of phenolic antioxidants from natural herbs often result in low yields, high toxicity, and pose environmental hazards limiting their effectiveness and scalability. Therefore, green extraction techniques using deep eutectic solvents, composed of natural, non-toxic, and biodegradable components were applied for extraction of chlorogenic acid from sea buckthorn weed. Fourteen deep eutectic solvent mixtures were prepared and evaluated for extraction yield of chlorogenic acid. Parameters such as hydrogen bond donor-to-hydrogen bond acceptor ratio, liquid-to-solid ratio, shaking speed, and shaking time were optimized for the best mixture. Results The combination of lactic acid and maltose (1:1) was found to give best extraction yield using response surface methodology. The deep eutectic solvent system under optimum conditions produced 12.2 g/100 g of crude extract sea buckthorn containing 174.7 mg gallic acid equivalents (mg GA)/g) of extract. Moreover, the optimized extract exhibited appreciable radical scavenging capacity (91%), trolox equivalent antioxidant capacity (11.2% of extract), and inhibition of peroxide in linoleic acid (80.6%). High-performance liquid chromatography-based characterization revealed the extracts contained chlorogenic acid (20.1 mg/g of extract) as the major constituent. Conclusions In summary, the adoption of DES for the extraction of bioactive phenolic constituents from sea buckthorn offers multiple benefits, including economic efficiency, enhanced extraction performance, and environmental sustainability. The findings of this study not only advance the understanding of DES in phytochemical extraction but also pave the way for broader application of green solvents in the natural products industry. Future research should focus on further optimizing DES formulations and scaling up the extraction process to fully realize the potential of this innovative extraction method in commercial applications.